Understanding the Role of Communication Strategy For effective Compliance in Case of Complementary and Alternative Medicine Industry - Anirudh, Gaur (2007)
Alternative medicines have been growing popular in recent times among consumers who want to take the responsibility of their health in their own hands (Siahpush 1999). Consumers are willing to go for non-technological and inexpensive therapies but there are issues of consumer compliance. By understanding and addressing this issue of consumer compliance in case alternative medicines, health care providers have an opportunity to improve patient compliance in case of alternative medicines. The objective of the study was to examine a communication strategy model, which involves using direct to consumer advertising as a way to influence consumer and specifically includes factors that can potentially improve compliance among alternative medicines users. Adult population which has been using alternative medicines was classified into two groups, Information-active and Information-passive on the basis their information seeking behaviour. A combination of quantitative and qualitative technique, involving structured questionnaire and semi-structured questionnaire based interviews was used to collect and analyse responses. It was found to be the most appropriate method as it was able to draw out the insights of the respondents. The majority of the findings were consistent with the relevant literature. The findings indicate the influence of these factors on compliance, as alternative medicines users are found to engage themselves in life styles that helps them in living a naturally healthy life and further point out that alternative medicine users are willing to comply with the treatment provided they experience symptom of relief from the treatment.